Prevalence of Thyroid Dysfunction in Chronic Hepatitis C Patients on Interferon Therapy - Ali Shuaib Ashraf, Ali Hassan, Muhammad Hamza Saeed, Arsalan Shamim, Haleem Hammad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to record the prevalence of thyroid dysfunction in chronic HCV cases receiving interferon therapy Methodology: A total of 100 patients with a diagnosis of chronic Hepatitis C between 35-70 years of either sex with normal Thyroid function test at the time of commencement of therapy were included. This trial was conducted during the period 2021-22 at Services Hospital Lahore. Interferon alfa 3 million units were administered to patients three times per week, along with oral ribavirin 1000 mg or 1200 mg every day (depending on their weight) for 24 weeks. During therapy, these individuals had clinical evaluations every 2, 4, and 6 months. The presence and severity of adverse events were evaluated at each visit, along with standard laboratory tests. TSH levels were used to assess patients for thyroid illness every 2, 4, and 6 months. Results: Mean age was calculated as 48.57+11.35 years, 52(52%) were male and 48(48%) were females, frequency of thyroid dysfunction in Chronic HCV cases receiving interferon therapy was recorded in 19(19%) of the cases. Conclusion: The incidence of thyroid dysfunction in individuals taking interferon treatment for chronic hepatitis C infection is not very high. However, we recommend that those who are currently receiving treatment for chronic hepatitis C should be evaluated for thyroid dysfunction. Keywords: Chronic Hepatitis C infection, Interferon therapy, Thyroid Dysfunction,